2012
DOI: 10.1002/hyp.9284
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the potential of reservoir outflow management to reduce sedimentation using continuous turbidity monitoring and reservoir modelling

Abstract: In‐stream sensors are increasingly deployed as part of ambient water quality‐monitoring networks. Temporally dense data from these networks can be used to better understand the transport of constituents through streams, lakes or reservoirs. Data from existing, continuously recording in‐stream flow and water quality monitoring stations were coupled with the two‐dimensional hydrodynamic CE‐QUAL‐W2 model to assess the potential of altered reservoir outflow management to reduce sediment trapping in John Redmond Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 23 publications
0
22
0
1
Order By: Relevance
“…Analysis of historical operations during 48 flood events plus modeling showed that a measurable increase in sediment throughput could be achieved by making relatively minor changes to the operating rule, while still maintaining downstream flood control targets [ Lee and Foster , ]. Compared to the conventional reservoir operation, “the altered scenario purposefully minimized reservoir elevation and residence time through larger, more rapid releases of water after periods of high inflows,” resulting in measurably decreased trap efficiency [ Lee and Foster , :1437]. This reduction in sediment trapping efficiency is achieved without any structural modifications, by simply including a sediment management objective in the reservoir operating rule.…”
Section: Reservoir Sediment Management Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of historical operations during 48 flood events plus modeling showed that a measurable increase in sediment throughput could be achieved by making relatively minor changes to the operating rule, while still maintaining downstream flood control targets [ Lee and Foster , ]. Compared to the conventional reservoir operation, “the altered scenario purposefully minimized reservoir elevation and residence time through larger, more rapid releases of water after periods of high inflows,” resulting in measurably decreased trap efficiency [ Lee and Foster , :1437]. This reduction in sediment trapping efficiency is achieved without any structural modifications, by simply including a sediment management objective in the reservoir operating rule.…”
Section: Reservoir Sediment Management Strategiesmentioning
confidence: 99%
“…1002/2013EF000184 2013. Compared to the conventional reservoir operation, "the altered scenario purposefully minimized reservoir elevation and residence time through larger, more rapid releases of water after periods of high inflows," resulting in measurably decreased trap efficiency [Lee andFoster, 2013:1437]. This reduction in sediment trapping efficiency is achieved without any structural modifications, by simply including a sediment management objective in the reservoir operating rule.…”
Section: Sediment Sluicingmentioning
confidence: 99%
“…As the model assumes lateral homogeneity, it is best suited for relatively long and narrow waterbodies exhibiting longitudinal and vertical water quality gradients. This model has been successfully applied to stratified water systems, including lakes, reservoirs, and estuaries (Afshar et al, 2013;Berger and Wells, 2008;Bowen and Hieronymus, 2003;Choi et al, 2007;Kuo et al, 2006;Lee and Foster, 2013;Park et al, 2014;Wells et al, 2012). The CE-QUAL-W2 model was selected in this study because it is appropriate for XXB, where lateral variations in velocity and temperature are insignificant (Yang et al, 2010).…”
Section: Model Description and Applicationmentioning
confidence: 99%
“…The relation between reservoir releases, water residence time, and sediment trapping efficiency may be used to manage reservoir sedimentation. Lee and Foster (2012) estimated that trapping efficiency of the reservoir could be decreased approximately 3 percent per year (equating to 56 acre-feet of storage) from current rates by altering outlet management practices specifically to reduce residence times within the reservoir.…”
Section: Sediment Trapping Efficiencymentioning
confidence: 99%